A cross-level model of legitimacy-driven institutional change: A case study in China's photovoltaic industry. Issue 3 (24th February 2020) - Guo, Yan; Chen, Liran; Fang, Shih-Chieh; Yang, Chen-Wei
Abstract : Purpose: The purpose of this study is to develop a cross-level model of legitimacy-driven institutional change in a Chinese management context; in other words, changes that start out as legitimacy gaining processes by green enterprises but result in a shift in field-level market logic. Design/methodology/approach: A case study using a historical inquiry approach and in-depth interviews has been used to qualitatively analyze the authors' case in the Chinese photovoltaic industry. Findings: The study proposes a cross-level explanation of institutional change by demonstrating how institutional change can create market forces at a field level that seemingly originate from an increase in the number of legitimated enterprises. This may negatively influence enterprises' ongoing legitimacy gaining process for their survival at the organizational level in an institutional environment. Research limitations/implications: The theoretical perspective helps improve descriptions of institutional change and develop a much-needed multi-level understanding of green enterprises in the highly institutionalized green industry. However, this case study may raise the concern of generalizability; thus, an additional survey is necessary. Practical implications: As organizational field-level market forces are endorsed and transformed in the legitimacy gaining activities of green enterprises, a green enterprise manager should be aware of its negative impact on their legitimacy gaining process and ultimate survival. Originality/value: The authors' model proposes a cross-level explanation of institutional change by demonstrating how institutional change can create market forces at a field level that seemingly originate from an increase in the number of legitimated enterprises. Consequently, this may negatively influence the enterprises' legitimacy gaining process.